Cell Wall Invertase 3 Affects Cassava Productivity via Regulating Sugar Allocation From Source to Sink - Yan, Wei; Wu, Xiaoyun; Li, Yanan; Liu, Guanghua; Cui, Zhanfei; Jiang, Tailing; Ma, Qiuxiang; Luo, Lijuan; Zhang, Peng (Frontiers in Plant Science, 2019)
Storage roots are the main sink for photo-assimilate accumulation and reflect cassava yield and productivity. Regulation of sugar partitioning from leaves to storage roots has not been elucidated. Cell wall invertases are involved in the hydrolysis of sugar during phloem unloading of vascular plants to control plant development and sink strength but have rarely been studied in root crops like cassava. MeCWINV3 encodes a typical cell wall invertase in cassava and is mainly expressed in vascular bundles. The gene is highly expressed in leaves, especially mature leaves, in response to diurnal rhythm. When MeCWINV3 was overexpressed in cassava, sugar export from leaves to storage roots was largely inhibited and sucrose hydrolysis in leaves was accelerated, leading to increased transient starch accumulation by blocking starch degradation and reduced overall plant growth. The progress of leaf senescence was promoted in the MeCWINV3 over-expressed cassava plants with increased expression of senescence-related genes. Storage root development was also delayed because of dramatically reduced sugar allocation from leaves. As a result, the transcriptional expression of starch biosynthetic genes such as small subunit ADP-glucose pyrophosphorylase, granule‐bound starch synthase I, and starch branching enzyme I was reduced in accordance with insufficient sugar supply in the storage roots of the transgenic plants. These results show that MeCWINV3 regulates sugar allocation from source to sink and maintains sugar balance in cassava, thus affecting yield of cassava storage roots.